The Level of Understanding of Tajwid Knowledge on Al-Quran Reading Skills: Tingkat Pemahaman Ilmu Tajwid terhadap Keterampilan Membaca Al-Quran - Mappanyompa (Halaqa: Islamic Education Journal, 2022)
Describe the level of knowledge of tajwid science on the ability to read the Koran in the Ahsanul Qolbu Mushallah Griya Sehati Housing which is the aim of this study. This investigation is a field study that combines relevant subjectivity with contextual investigation methodology. Subjective analysis that highlights important aspects of the research cycle and develops a thorough understanding of people, encounters, or situations that have occurred, are occurring, or will occur. The consequences of this study, in particular the level of understanding of information on the Tajwid Jama'ah Mushallah Ahsanul Qolbu housing at Griya Sehati Housing, is divided into two classes, namely the first: the category of low congregation capacity; a), regarding mastering the Al-Qur'an starting from mastering the quality of hijaiyah letters. b), how to pronounce hijaiyah letters, how to use punctuation, how to speak lam ta'rif, qolqolah, laful jalalah, gunnah, waqaf, and ibtida', the law of breadfruit or tanwin, namely mim breadfruit, pious, special, and the law of reading frantically far'i is reckless, reads idghom, reads gharib b), namely in memorizing Juz 30, which is only allowed a maximum of 5 to 10 letters. d), the use of drill and exhibition, talakqi, question and answer, critical thinking, and lecture strategy. Second: "Classes have moderate to good capacity in this Tahsin class in general. The standards for assessment skills are the same as general education classes, but there are several advantages, such as the ability to understand textbooks that include challenging material, such as reading naql, nun wiqoyah, saktah, and tahsin. This indicates that the subject matter is well understood, so the teaching begins by discussing the law of tajwid directly, starting from lam ta'rif to reading gharib, and they also memorize Juz 30.